Performing Continuity of/in Smart Infrastructure : Exploring Entanglements of Infrastructure and Actions - Niemimaa, Marko (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2017)
Nearly everything we do in contemporary organizations and societies builds on some form of infrastructure. Our reliance on infrastructures underscores the importance of the continuity of these infrastructures. However, the infrastructures are inherently unreliable and unpredictable and achieve veneers of permanence and stability only through constant and ongoing efforts. In their functioning, they become established through complex and uncertain processes that involve a number of actors and factors. Consequently, understanding those processes is a key concern for organizations that are responsible for these infrastructures. Traditionally, the literature on the business continuity of organizational functions has emphasized the importance of planning and management approaches. Practitioners and academics have brought forth frameworks to aid organizations in planning and managing their continuity-related issues. The frameworks offer universally applicable processes and procedures that organizations should follow to improve their continuity. However, these frameworks tell little about continuity itself. Organizations rarely function as they document or as management describes organizational work. As such, the complex and uncertain processes of continuity cannot be directly inferred from the documents or from the managerial descriptions of work. If we wish to enact meaningful changes to those complex and uncertain processes through which infrastructure continuity becomes established, we need to understand how those processes unfold in practice. This dissertation focuses on infrastructure continuity in a smart infrastructure context. Smart infrastructures are traditional infrastructures that have been extended with digital technologies. In this research, infrastructure continuity is approached from the perspective of technicians working in the smart infrastructure context. The technicians’ work in these contexts is constitutively entangled with information systems and the technologies that form the infrastructures. As such, the smart infrastructures form an intriguing and fruitful yet rather unexplored context for information systems research. Theoretically, this research builds on sociomaterial theorizing and especially on Karen Barad’s agential realism. The purpose of this dissertation is to increase understanding on how the continuity of smart infrastructure becomes performed. This purpose is explored through six research articles that form the foundations of this dissertation. Methodologically, this research builds on conceptual and empirical research approaches. The conceptual research focuses on developing and clarifying business continuity- and sociomateriality-related concepts and approaches through argumentation and a literature review. The empirical research builds on a qualitative research approach and, more specifically, on ethnographic research. As is typical for ethnographic research, the empirical material was collected from a single organization that was studied extensively over a several-month participant observation. Reflecting the purpose of the study, the ethnography was conducted in a centralized operations center of a smart infrastructure (smart power grid) where technicians work with information systems and technologies. This dissertation contributes to the literature on infrastructure continuity and on sociomateriality. The primary contribution to the infrastructure continuity literature is a performative conceptualization of the infrastructure continuity. This conceptualization suggests that business continuity is not an attribute of any single measure but is an outcome of a joint accomplishment of sociomaterial networks of agencies that becomes established through recurrent actions. As such, the findings of this research challenge some of the taken-for-granted assumptions embedded in the literature but also extend the earlier literature. In addition, this dissertation extends discussions on sociomaterial agency. In the light of the findings, when agency is situated in the context of a smart infrastructure, agency becomes historic, polycentric, dynamic, and discontinuous.

Lähes kaikki mitä me teemme nyky-yhteiskunnassa nojaa infrastruktuureihin. Voimmekin sanoa elävämme keskellä infrastruktuurien verkostoa. Riippuvaisuutemme infrastruktuureista korostaa niiden toiminnan jatkuvuuden tärkeyttä. Nämä infrastruktuurit ovat kuitenkin perustaltaan epäluotettavia ja arvaamattomia. Niiden toimivuus syntyy monimutkaisten ja epävarmojen prosessien kautta, jotka sisältävät moninaisia toimijoita ja tekijöitä. Näiden prosessien ymmärtäminen on keskeistä organisaatioille, jotka vastaavat näistä infrastruktuureista. Perinteisesti kirjallisuudessa, joka keskittyy toiminnan jatkuvuuteen (eng. business continuity), on korostettu suunnitelmien ja hallinnoinnin merkitystä. Suunnitteluun ja hallinnointiin on kehitetty useita johtamisen viitekehyksiä. Ne tarjoavat universaaleiksi tarkoitettuja määrämuotoisia prosesseja ja menettelytapoja, joita organisaatioiden tulisi noudattaa. Nämä viitekehykset kertovat kuitenkin hyvin vähän siitä mitä tai miten toiminnan jatkuvuus itsessään käytännössä ilmenee. Organisaatiot harvoin toimivat kuten dokumentoivat tai kuten organisaatioiden johto kuvailee toimintaa, joten näistä ei voida suoraan päätellä organisaation toimintaa. Kuitenkin jos haluamme toteuttaa merkityksellisiä muutoksia niihin monimutkaisiin ja epävarmoihin prosesseihin, joiden kautta toiminnan jatkuvuus syntyy, meidän tulee ymmärtää paremmin näitä prosesseja käytännössä. Tässä tietojärjestelmätieteisiin sijoittuvassa väitöskirjassa keskitytään toiminnan jatkuvuuteen älykkäiden infrastruktuurien (eng. smart infrastructure) kontekstissa. Älykkäillä infrastruktuureilla tarkoitetaan tässä tutkimuksessa perinteisiä infrastruktuureja, kuten sähköverkkoja, vedenjakelua, ja tieverkostoa, jotka ovat digitalisoitu. Aihetta lähestytään erityisesti infrastruktuurin parissa toimivien teknikoiden työn kautta. Teknikoiden työ näissä ympäristöissä on nivoutunut kiinteästi yhteen tietojärjestelmien ja teknologioiden kanssa, jotka muodostavat infrastruktuurin. Älykkäät infrastruktuurit muodostavatkin näin erityisesti tietojärjestelmätieteiden tutkimukselle kiinnostavan, mutta vähän tutkitun kontekstin. Tutkimus pohjautuu teoreettisesti sosiomateriaalisuuteen ja nojaa erityisesti Karen Baradin filosofiseen ja teoreettiseen viitekehykseen toimijarealismista (eng. agential realism). Tutkimuksen tavoite on tuottaa ymmärrystä siitä, miten infrastruktuurien jatkuvuus toteutuu käytännössä. Tätä tavoitetta on tässä väitöskirjassa tutkittu kuuden vertaisarvioidun artikkelin kautta. Menetelmällisesti tutkimuksessa on nojattu sekä konseptuaaliseen että empiiriseen tutkimukseen. Konseptuaalinen tutkimus keskittyy toiminnan jatkuvuuden ja sosiomateriaalisuuden käsitteiden ja lähestymistapojen kehittämiseen sekä selventämiseen argumentoinnin ja kirjallisuuskatsauksen avulla. Empiirinen tutkimuspohjautuu laadulliseen tutkimusotteeseen ja nojaa etnografiseen tutkimusmenetelmään. Kuten etnografiselle tutkimusmenetelmälle on luonnollista, aineisto pohjautuu pääosin osallistuvaan havainnointiin yhdessä organisaatiossa, jota on tutkittu intensiivisesti. Heijastaen tutkimuksen tavoitetta ja ongelmanasettelua, etnografinen tutkimus suoritettiin älykkään infrastruktuurin (sähköverkon) keskitetyssä valvomossa, jossa teknikoiden työtä tietojärjestelmien ja teknologioiden parissa seurattiin useiden kuukausien ajan. Tutkimuksen tulokset osallistuvat infrastruktuurien toiminnan jatkuvuuden ja sosiomaterialisuuden keskusteluihin. Tutkimuksen keskeisin tulos toiminnan jatkuvuuden tutkimukseen on toiminnan jatkuvuuden konseptualisointi suoritettuna toimintana. Tämän konseptualisoinnin mukaan toiminnan jatkuvuus ei ole jonkin menetelmän ominaisuus vaan jatkuvuus tuotetaan yhteisesti sosiomateriaalisessa toimijoiden verkossa toistuvien tekojen kautta. Tutkimuksen tulokset siis haastavat mutta myös edistävät aiempaa kirjallisuutta toiminnan jatkuvuudesta. Lisäksi, tutkimuksen tulokset edistävät keskusteluita toimijuuden sosiomateriaalisuudesta. Tulosten valossa, kun toimijuutta tarkastellaan infrastruktuurikontekstissa, on toimijuus historiallinen, polysentrinen, dynaaminen ja yllätyksellinen.